Upaya Pengembangan Dalam Meningkatkan Daya Saing Usaha UMKM Lokal Desa Telajung - MH Ainulyaqin; Adrianna S. R; Sukron Mamun; Ramadhan F; Dede M (LPPM STEBIS YPII, 2025)
This research is related to the development of micro and small enterprises in Telajung village. The focus of Indonesia's national economic development is micro, small and medium enterprises (MSMEs). Small, medium and micro enterprises are the backbone of the community's economic system in poverty alleviation, whose development can expand the economic base and make a significant contribution to increasing the resilience of the regional economy and the national economy. In order for MSMEs in Telajung Village to survive or compete in the flow of free trade, an appropriate strategy model is needed to sustain the existence of MSMEs in Telajung Village. The development of small, medium, and micro enterprises in rural areas has new potential in creating jobs, stimulating regional economic growth, and narrowing economic disparities.